Iklan lampau Indonesia dalam wujud komik Analisis bahasa dan grafis - Alkatiri, Zeffry (Wacana, Journal of the Humanities of Indonesia, 2005)
As a powerful medium to persuade people to buy a product or service, ads have long been used in many forms. This study attempts to understand the language use and graphic design of comic as one of the ads forms in Jakarta-based Indonesian media, particularly in the period of 1940-1960s. By employing different approaches in Linguistic Anthropology, Mass Communication and Graphic Design, the findings show a close relationship between the language and the graphic design of the ads with the society who consumed them as well as a trend towards informal language use and popular culture.